Monaco : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This report provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in the Principality of Monaco. The Principality has a satisfactory legal framework to combat money laundering and terrorist financing though, in general, the legal provisions are not detailed or otherwise supplemented by detailed secondary legislation and instructions. The 2003 money laundering offence's restrictive terms hindered prosecutions, and thus the results in terms of convictions for money laundering remained disappointing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet